Rare bird documentation form for Peregrine Falcon at Fairfield, 1991 - Alexander, Carol Annet al (1991)
Rare bird documentation form for a Peregrine Falcon at Fairfield in Jefferson County, IA on January 18, 1991. Epson - sheet feed